Notes on the Ogham Inscription on the Newton Stone (Proceedings of the Society of Antiquaries of Scotland, 1865)
This article begins with an overview of Ogham, citing several examples standing stones on which Ogham inscriptions are found. Having examined this writing system, the author moves on to describe the Ogham inscription on the Newton Stone and attempt a translation. He ends with some speculation around the names found in the inscription and the possible date the stone was carved.